2003
DOI: 10.1258/000456303770367270
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and technical evaluation of the ACS:OV serum assay and comparison with three other CA125-detecting assays

Abstract: Background In this study the clinical and technical performance of the CA125-detecting Bayer ACS:OV immunoluminometric serum assay was compared with three other well-established CA125-detecting assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…All of these previous studies used first-generation kits for CA125 that are no longer in use. In three of them (Davelaar et al, 2003;Kobayashi et al, 1993;Yan et al, 1999) investigators reported higher relative differences in CA125 than what we found. In five of these studies (Bonfrer et al, 1994;Clement et al, 1995;Hornstein et al, 1996;Lehtovirta et al, 1990;van Kamp et al, 1993) investigators reported relative differences of CA125 using multiple assay systems that were similar to the patterns we observed.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…All of these previous studies used first-generation kits for CA125 that are no longer in use. In three of them (Davelaar et al, 2003;Kobayashi et al, 1993;Yan et al, 1999) investigators reported higher relative differences in CA125 than what we found. In five of these studies (Bonfrer et al, 1994;Clement et al, 1995;Hornstein et al, 1996;Lehtovirta et al, 1990;van Kamp et al, 1993) investigators reported relative differences of CA125 using multiple assay systems that were similar to the patterns we observed.…”
Section: Discussioncontrasting
confidence: 69%
“…Previous studies have reported varying relative differences in CA125 values using different assay systems with different epitope-antibody recognition sites (Bonfrer et al, 1994;Clement et al, 1995;Davelaar et al, 2003;Hornstein, Goodman, Thomas, Knapp, & Harlow, 1996;Kobayashi, Tamura, Satoh, & Terao, 1993;Lehtovirta et al, 1990;van Kamp et al, 1993;Yan et al, 1999). All of these previous studies used first-generation kits for CA125 that are no longer in use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as relating specifically to the original CA125 assay, it was based on the 99th percentile for a population of premenopausal women aged between 18 and 40 years of age. Several authors have described that serum CA125 levels fall following the menopause [90][91][92][93] and that the lower postmenopausal cut-off is similar to that for men [94,95]. The issue of an appropriate reference interval is vital to the optimal use of the test because the higher reference limits defined in premenopausal women are very often inappropriately applied to postmenopausal women (more commonly suffering from ovarian cancer) or men (more commonly suffering from cardiac failure).…”
Section: Reference Intervalsmentioning
confidence: 99%